2021
DOI: 10.1186/s13731-021-00170-8
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurial networks, entrepreneurial orientation, and performance of small and medium enterprises: are dynamic capabilities the missing link?

Abstract: Performance of small and medium enterprises (SMEs) has been addressed widely in the literature. Both developed and developing countries are highly concerned about the growth and performance of SMEs. The literature exploring performance is abundant, however, has certain controversies. To identify the reasons behind those controversies, this study was conducted with the aim being to identify the mediating role of dynamic capabilities which are developed by entrepreneurial networks and entrepreneurial orientation… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
61
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(69 citation statements)
references
References 46 publications
3
61
0
5
Order By: Relevance
“…Some other recent works (Yahya et al 2021;Abu-Rumman 2021;Abu-Rumman et al 2021;Aldiabat et al 2018Aldiabat et al , 2019Rashid et al 2021;Chen et al 2019;Wang et al 2018;Zhao et al 2018;Zhang et al 2018a) reported those are based on blockchain for the medical data storage and sharing in the cloud computing environment. The blockchain-based data-sharing framework proposed in Yahya et al (2021) that adequately approaches the access control difficulties connected with sensible medical data collected in the cloud employing built-in and immutability independence features of the blockchain.…”
Section: Block Chain-based Healthcare Systemsmentioning
confidence: 99%
“…Some other recent works (Yahya et al 2021;Abu-Rumman 2021;Abu-Rumman et al 2021;Aldiabat et al 2018Aldiabat et al , 2019Rashid et al 2021;Chen et al 2019;Wang et al 2018;Zhao et al 2018;Zhang et al 2018a) reported those are based on blockchain for the medical data storage and sharing in the cloud computing environment. The blockchain-based data-sharing framework proposed in Yahya et al (2021) that adequately approaches the access control difficulties connected with sensible medical data collected in the cloud employing built-in and immutability independence features of the blockchain.…”
Section: Block Chain-based Healthcare Systemsmentioning
confidence: 99%
“…As the level of knowledge against COVID-19 contamination increases during the pandemic process, more active performance is demonstrated with fewer units in the fight against the disease (Assadian et al 2021;Kulle et al 2021;Chen and Ray 2021;Mallah et al 2021;Kaye et al 2020). In this way, other elective health services are also provided (Abu-Rumman 2021;Abu-Rumman et al 2021;Matsuyama et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays (Alhayani and Abdallah 2020; Alhayani and llha 2021;Al-Hayani and Ilhan 2020), BC has engrossed substantial interest in research regions outside the financial sector such as IoT using its characteristics of decentralization, security, and auditability though, despite the attempts there seems to be a lacking relation towards constructing a actually reorganized (Kwekha- Rashid et al 2021;Hasan and Alhayani 2021;Yahya et al 2021), unworthy and protected environment for the IoT (Sathiyanathan et al 2020;Dorri et al 2016). The IoT devices arrayed with their existing username password combination for the authentication purpose (Abu-Rumman 2021; Abu-Rumman et al 2021). Therefore, it becomes vulnerable to attack and can be controlled.…”
Section: Introductionmentioning
confidence: 99%